Dual malignancies in Lynch Syndrome: a rare case of synchronous colorectal and ovarian cancer highlighting the potential role of immunotherapy - Jian, Ng Kai; Mohammad Rizzuan, Mohammad Qisti Khairi; Jian, Low Qin (Faculty of Medicine, 2026)
We report a 35-year-old woman with dual malignancies associated with Lynch Syndrome, diagnosed with Stage IIIC sigmoid colon adenocarcinoma and Stage IIA left ovarian serous papillary adenocarcinoma. Germline testing revealed MSH2 gene mutation, particularly exon 7 deletion. This case highlights the importance of early detection, germline testing and individualized management strategies for Lynch Syndrome patients. It also underscores the potential of immunotherapy as an effective therapy for recurrent Lynch-associated cancers, emphasizing the need for continuous research into novel therapeutic modalities.